Psychological distress differentiates subjective health within a vulnerable subgroup of patients with immune-mediated inflammatory diseases - Tessa S. Folkertsma; Eline J. Mertens; Damien S. E. Broekharst; Robert M. Vodegel; Greetje J. Tack; Maya J. Schroevers; Sjaak Bloem; Reinhard Bos (Frontiers in Psychology, 2026)
Background Patients with immune-mediated inflammatory diseases (IMIDs) who score low on both acceptance and perceived control are classified as segment 4 in the Subjective Health Experience (SHE) model. They represent the most psychologically vulnerable group. Prior work in oncology has identified heterogeneity within this segment, but whether similar differentiation exists in IMIDs remains unknown. Therefore, the present study examines heterogeneity within SHE segment 4 in IMIDs by comparing moderate and severe subgroups on psychological and disease-related outcomes. Methods A cross-sectional survey was conducted among 500 Dutch adults with physician-confirmed IMIDs. Of these, 166 were classified in segment 4 and subdivided into moderate ( n = 96) and severe ( n = 70) subgroups based on median acceptance and control scores. Group differences in psychological (i.e., subjective health, Health-Related Quality of Life (HRQoL), psychological distress) and disease-related outcomes (i.e., self-reported disease severity and activity) were assessed using t -tests and chi-square analyses. Multiple linear regression analyses were performed to determine whether subgroup differences remained after adjustment for demographic and clinical characteristics. Results The severe subgroup reported a significantly poorer subjective health, lower HRQoL, and higher levels of anxiety, depression, and overall psychological distress, compared with the moderate subgroup. These associations remained significant after adjustment for age, gender, education, diagnosis, and comorbidity burden. No significant differences were observed in disease activity, disease impact, or comorbidity burden. Exploratory diagnosis-specific analyses suggested that subgroup differences were present across diagnoses, although subgroup sizes were limited. Conclusion Meaningful psychological heterogeneity exists within SHE segment 4 in IMIDs and appears to be primarily related to psychological distress and quality of life rather than disease-related factors. These findings support the potential value of the SHE model for identifying patients who may benefit from personalized supportive care.